Elisão tributária no ordenamento jurídico brasileiro - Carvalho, Ivo César Barreto de (2004)
It reports a tax avoidance study on the brazilian juridical ordinance and its methodology on the concepts settlement such as elision, evasion, elusion, fiscal concealment, fiscal fraud, tributary planning, fiscal avoidance among many others. The juridical nature of the juridical institutes is analyzed concerning to evasion, elision and tributary elusion, determining therefore the essential term premises, which are used on the present thesis. It is also made an approach of the methodological fundamentais of the general antiavoidance rule, whose present doctrinaires of the Fiscal Law interpretation are made basically by three positions: the jurisprudence concepts, the jurisprudence interests and the jurisprudence merit. In relation to the development of these interpretaiions, the general anti-avoidance rule is analysed through the analogical, extensive and theological interpretation. Thus, the anti-avoidance rule on the juridical ordinance study is spread among many other countries. Based on the juridical ordinance, initial studies were done in order to include the anti-avoidance rule in Brazil, eventhough they were preceded by some prevention rules toward the tributary elusion. After, the unique clause of the article 116 of the National Tax Code, included by the Complementary Law number 104, from January the 1st, 2001, and also the first attempt to regulate this matter through Provisional Law number 66, from August the 29^, 2002, are analyzed. From the analysis, it is understood that the general anti-avoidance rules, such as legal provision of the unique clause of the article 116 of the National Tax Code, included by the Complementary Law number 104/2001, are not well adequated to the brazilian juridical ordinance in order to disconsider juridical acts and contracts which are formulated by the tax payers aiming the fiscal objectives, beyond the fraud law and case simulations. Due to this first conclusion, it is understood that the tax planning is a tributary economy perfectly legitimate technique, based on the Constitution. Therefore, if the general antiavoidance rule regulation overpass the boundaries and the legal parameters, the constitutional principies of legality, characteristic, isonomy, power separation, juridical security, proportion, good faith and the prohibition confiscation will all be injured. Regarding to the extrafiscal policies, it must be concluded that the extrafiscal taxation concluded that the individual can practice legitimately the tax avoidance (tax planning) without injuring the Public Administration. In addition to the comparison of the general anti-avoidance rule and the institutes of the civil law, it must be concluded that they are compatible. Finally, because of the great divergence between the Welfare State and the Neoliberal State, the effective structure and development of the Democratic State of Law is the pathway to the development of a country, being the general anti-elusion rule one of the devices to such realization.